Decision Support System For Determining The Best Employees To Get Incentives Using The Web-Based Multi Factor Evaluation Process (MFEP) Method - Dimas Prananda; Warih Utami, Ardhini (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
One way for companies to enhance employee performance and motivation is by discovering the most effective methods of providing incentives. However, due to the multitude of factors that must be considered, this process is often complex. Therefore, the objective of this research is to create and develop a web-based Decision Support System that employs the Multi-Factor Evaluation Process (MFEP) method to assist in determining the employees who are most deserving of compensation. This research leverages the Rapid Application Development (RAD) methodology, which encompasses several phases: requirements planning, user design, construction, and cutover. During the construction phase, the system was tested using the Blackbox method to ensure that all functions operated correctly without examining the program code. The research findings indicate that the decision support system can recommend the employees who are most eligible for compensation in accordance with company standards. The MFEP method implemented in this system yields unbiased evaluation results by considering various assessment factors. The rapid system development (RAD) method facilitated a swift and structured development process. The results of the Blackbox testing demonstrate that the system operates effectively in line with the established requirements. With this system, it is anticipated that the process of identifying top-performing employees will become more efficient, objective, and transparent. Additionally, this system can enhance employee motivation to achieve the highest levels of performance.